Functionalized fabric

By using functional fabrics and low-temperature forming technology of fluorescent materials in the production of wind turbine blades, the production efficiency and consistency of wind turbine blades is solved, and efficient production and quality control are achieved.

CN119173657APending Publication Date: 2024-12-20OWENS CORNING INTELLECTUAL CAPITAL LLC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380039086.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-23
Filing Date
2023-03-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the production of wind turbine blades, increasing the blade size leads to problems of production efficiency and consistency, and traditional methods are time-consuming and difficult to ensure quality control.

Method used

Using a functionalized fabric containing fluorescent material, a forming part is formed by applying a fluorescent binder to the fibrous fabric and heating at low temperatures, the adhesive distribution is evaluated to improve production efficiency and quality control.

Benefits of technology

The production efficiency of wind turbine blades is significantly improved, mechanical characteristics are maintained, and better quality control is achieved through the evaluation of the distribution of fluorescent binder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173657A_ABST
    Figure CN119173657A_ABST
Patent Text Reader

Abstract

Described herein is a functionalized fabric comprising a fibrous fabric and a binder comprising, consisting of, or consisting essentially of a fluorescent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to functionalized fabrics comprising glass fibers and / or carbon fibers and their production, in particular functionalized fabrics for reinforcing structural components, such as wind turbine components. Background Art

[0002] It is well known that glass fibers and / or carbon fibers may be used to form reinforcing fiber fabrics to reinforce structural components such as wind turbine blades or related components (eg, spar caps).

[0003] Structural components comprising reinforcing fiber fabric (reinforced structural components) are typically formed by stacking layers of reinforcing fiber fabric in a mold, filling the mold with resin, and curing the resin to form the component. This process can be time consuming.

[0004] As the search for alternative energy sources continues, the use of wind energy and wind turbines has received increasing attention. As interest in harnessing wind energy to generate more energy has grown, technological advances in the field have allowed for increased sizes of wind turbine blades. Increasing the size of wind turbine blades also increases the time required to produce wind turbine blades and can raise issues related to consistency and quality control.

[0005] It would be desirable to provide improvements in enhancing the efficiency and consistency of the production of structural components, such as wind turbine blades. Summary of the invention

[0006] Most generally, the present invention provides functionalized fabrics comprising a fiber fabric and a binder and their production, wherein the binder comprises, consists of, or consists essentially of a fluorescent material (e.g., a UV fluorescent material). A binder comprising, consisting of, or consisting essentially of a fluorescent material may be referred to herein as a fluorescent binder.

[0007] In a first aspect, the present invention provides a functionalized fabric comprising:

[0008] Fabrics; and

[0009] a binder comprising, consisting of or consisting essentially of a fluorescent material,

[0010] The fiber fabric comprises: first fibers oriented along a first direction; and second fibers oriented along a second direction, wherein the first fibers include glass fibers and / or carbon fibers, the second fibers include glass fibers and / or carbon fibers, and the second direction is within 0 to 90 degrees of the first direction.

[0011] In a second aspect, the present invention provides a fabric laminate comprising at least two layers of a functionalized fabric as described herein.

[0012] In a third aspect, the present invention provides a shaped part comprising a fabric laminate as described herein.

[0013] In a fourth aspect, the present invention provides a method for producing a functionalized fabric, the method comprising:

[0014] Providing a fiber fabric, the fiber fabric comprising first fibers oriented in a first direction and second fibers oriented in a second direction, the second direction being within 0 to 90 degrees of the first direction, the first fibers comprising glass fibers and / or carbon fibers, and the second fibers comprising glass fibers and / or carbon fibers; and

[0015] A binder comprising, consisting of, or consisting essentially of a fluorescent material is applied to the fibrous web to provide a functionalized web.

[0016] In a fifth aspect, the present invention provides a method for producing a shaped part, the method comprising:

[0017] stacking multiple layers of the functionalized fabric described herein;

[0018] shaping the stacked plurality of fabric layers to form a shaped stack;

[0019] The shaped layup is heated at a temperature up to about 150°C to provide a shaped part.

[0020] In a sixth aspect, the present invention provides a composite article comprising a shaped part as described herein.

[0021] In a seventh aspect, there is provided a method of making a composite article, the method comprising impregnating a shaped part as described herein with a resin and curing the resin to form the composite article.

[0022] In an eighth aspect, there is provided a method of evaluating the distribution of fluorescent binders on a functionalized fabric as described herein by exposing the binders to light so that they fluoresce.

[0023] The light may be UV light.

[0024] The fluorescent binder can be viewed, detected or analyzed. For example, the fluorescent binder can be viewed, detected or analyzed by eye with or without assistance.

[0025] In any aspect of the invention, the fluorescent material may be a UV fluorescent material, or the fluorescent adhesive may be a UV fluorescent adhesive.

[0026] The method for assessing the distribution of the fluorescent binder may be part of a production method, such as an in-line method.

[0027] The present inventors have found that the present invention provides a functionalized fabric that provides improvements in the production efficiency of reinforced structural components, such as wind turbine blades and related components. The present inventors have also found that the present invention provides a means by which improved analysis and characterization is provided and which is reflected in related functionalized fabrics, formed parts and composite articles.

[0028] Furthermore, the present inventors have surprisingly found that a functionalized fabric comprising a small amount of a binder as described herein (e.g., less than 5 wt % (e.g., less than 3.5 wt % or 0.1 wt % to 3.5 wt %) and / or about 2 g / m 2 About 30g / m 2 (e.g. about 2 g / m 2 About 20g / m 2 ) functionalized fabric) and optionally having a fiber fabric with a glass transition temperature of up to about 75°C can be stacked and shaped (i.e., pre-formed) prior to incorporation into a reinforced structural component. It has been found that the provision of the functionalized fabrics described herein surprisingly increases the speed at which reinforced structural components (e.g., wind turbine blades) can be produced. Even more surprisingly, the inventors have found that the functionalized fabrics described herein can provide improvements in the efficiency of production of reinforced structural components (e.g., wind turbine blades) without adversely affecting the mechanical properties of the fabric or the final component.

[0029] The present inventors have also discovered that the use of a binder in the production of functionalized fabrics that fluoresces when exposed to electromagnetic radiation (such as UV light) provides a means by which the quality of the functionalized fabric (and related components) can be assessed in a straightforward manner.

[0030] The present invention includes any combination of aspects and preferred features described herein except where such a combination is expressly impermissible or expressly avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Embodiments and experiments illustrating the principles of the present invention will now be discussed with reference to the accompanying drawings, in which:

[0032] Figure 1 is a graph showing the particle size distribution of various binder particles that may be applied to a fiber fabric to produce a functionalized fabric as described herein;

[0033] Figure 2 is an image of the functionalized fabric described in this article generated by 3D microscopy;

[0034] Figure 3a and Figure 3b It is the image of the fluorescent binder on the surface of the fiber fabric;

[0035] Figure 4a is an image of the functionalized fabric described in this article generated by 3D microscopy;

[0036] Figure 4b It is shown Figure 4a A graph showing the binder particle size distribution on the surface of the functionalized fabric is shown. DETAILED DESCRIPTION

[0037] Various aspects and embodiments of the present invention will now be discussed with reference to the accompanying drawings. Additional aspects and embodiments will be apparent to those skilled in the art.

[0038] Described herein is a functionalized fabric comprising a fibrous fabric and a binder, wherein the binder comprises, consists of, or consists essentially of a fluorescent material.

[0039] Fabric

[0040] The fabric contains:

[0041] first fibers oriented in a first direction; and

[0042] second fibers oriented in a second direction,

[0043] The first fibers include glass fibers and / or carbon fibers, the second fibers include glass fibers and / or carbon fibers, and the second direction is within 0 to 90 degrees of the first direction.

[0044] The first fibers of the fiber fabric may be referred to as warp fibers. The first fibers may be arranged side by side and substantially parallel to each other. The second fibers of the fiber fabric may be referred to as weft fibers. The second fibers may be arranged side by side and substantially parallel to each other.

[0045] In an embodiment, the fiber fabric comprises first fibers oriented in a first direction and second fibers oriented in a second direction, wherein the second direction is within 0 to 90 degrees of the first direction, for example, within about 10 to about 90 degrees of the first direction, within about 20 to about 90 degrees of the first direction, within about 30 to about 90 degrees of the first direction, within about 40 to about 90 degrees of the first direction, within about 45 to about 90 degrees of the first direction, within about 60 to about 90 degrees of the first direction, within about 70 to about 90 degrees of the first direction, within about 80 to about 90 degrees of the first direction, within about 85 to about 90 degrees of the first direction, within about 88 to about 90 degrees of the first direction, or within about 90 degrees of the first direction.

[0046] In an embodiment, the fiber fabric may be a unidirectional fabric or a multi-axial fabric, such as a bi-axial fabric.

[0047] In an embodiment, the fiber fabric is a unidirectional fabric. The fiber fabric for a unidirectional fabric may include a second fiber oriented in a second direction, wherein the second direction is oriented in a direction greater than 0 degrees in the first direction. For example, the unidirectional fabric may include a first fiber oriented in a first direction and a second fiber oriented in a second direction, wherein the second direction is about 0 degrees to 90 degrees of the first direction, for example, within about 45 degrees to about 90 degrees of the first direction, within about 60 degrees to about 90 degrees of the first direction, within about 70 degrees to about 90 degrees of the first direction, within about 80 degrees to about 90 degrees of the first direction, within about 85 degrees to about 90 degrees of the first direction, within about 88 degrees to about 90 degrees of the first direction, or within about 90 degrees of the first direction. In a unidirectional fabric, the first fiber may account for more than about 90 weight % of the fiber fabric, for example, more than about 92 weight % of the fiber fabric, or at least about 95 weight % of the fiber fabric. In a unidirectional fabric, the second fiber may account for at most about 10 weight % of the fiber fabric, for example, at most about 8 weight %, or at most about 5 weight %. In a unidirectional fabric, the second direction may be substantially perpendicular to the first direction, the first fibers may comprise greater than 92% by weight of the fiber fabric, and the second fibers may comprise up to about 8% by weight of the fiber fabric. In an embodiment, the fiber fabric is a unidirectional fabric, the second direction is substantially perpendicular to the first direction, and the weight ratio of the first fibers to the second fibers is in the range of 15:1 to 25:1.

[0048] In an embodiment, the fiber fabric is a biaxial fabric. In a biaxial fabric, the second direction may be within about 20 degrees to about 90 degrees of the first direction, for example, the second direction may be within about 30 degrees to about 90 degrees of the first direction, the second direction may be within about 40 degrees to about 90 degrees of the first direction, the second direction may be within about 45 degrees to about 90 degrees of the first direction, the second direction may be within about 60 degrees to about 90 degrees of the first direction, within about 70 degrees to about 90 degrees of the first direction, within about 80 degrees to about 90 degrees of the first direction, within about 85 degrees to about 90 degrees of the first direction, within about 88 degrees to about 90 degrees of the first direction, or within about 90 degrees of the first direction. In an embodiment, the fiber fabric is a biaxial fabric, wherein the second direction is about 25 degrees to 75 degrees of the first direction, for example, about 45 degrees of the first direction. In an embodiment, the fiber fabric is a biaxial fabric, wherein the second direction is at least 45 degrees of the first direction. In an embodiment, the fiber fabric is a biaxial fabric, and the second direction is substantially perpendicular to the first direction. In embodiments where the fiber fabric is a biaxial fabric, the second fibers comprise greater than 5% by weight of the fiber fabric. In embodiments where the fiber fabric is a biaxial fabric, the second fibers may comprise at least about 10% by weight of the fiber fabric, such as at least about 15% by weight, at least about 20% by weight, or at least about 25% by weight of the fiber fabric.

[0049] In embodiments, at least the first fibers or the second fibers comprise, consist essentially of, or consist of glass fibers.

[0050] In embodiments, the glass fibers comprise at least about 50% by weight of the fiber fabrics described herein, e.g., at least about 60% by weight of the fiber fabric, at least about 70% by weight of the fiber fabric, at least about 80% by weight of the fiber fabric, at least about 90% by weight of the fiber fabric, or at least about 95% by weight of the fiber fabric.

[0051] The term "glass fiber" is used herein to refer to a plurality of continuous glass filaments (the term "continuous" as used herein is used to refer to fibers / filaments having a length many times longer than its diameter, for example at least about 5000 times longer than its diameter, for example about 10 000 times longer than its diameter). The glass fibers used in the fabrics described herein can be provided as glass fiber strands (or tows). The glass fibers can be formed by a continuous manufacturing process in which molten glass passes through the holes of a "buffer plate" and the molten glass stream formed thereby solidifies into filaments / fibers. The glass fibers described herein (e.g., the glass fibers of the first fibers and / or the second fibers) can include a sizing agent on their surface, for example, a sizing agent applied to the glass fibers during fiber formation. The sizing agent can include components that promote the formation of the glass fibers and / or their use in the matrix resin, such as a film former, a lubricant, a coupling agent (to promote compatibility between the glass fibers and the resin used to form the composite product comprising the hybrid fabric described herein), etc. In some embodiments, the glass fibers of the first fibers and / or the second fibers include a polyester compatible sizing or an epoxy compatible sizing.

[0052] As used herein, the term "glass fiber strand" or "glass fiber tow" refers to a bundle of continuous glass filaments. In an embodiment, the glass fiber strand or tow is a plurality of bundles of untwisted glass filaments.

[0053] In an embodiment, the glass fiber strands or glass fiber bundles are provided by glass fiber direct rovings. Glass fiber direct rovings consist of a bundle of continuous untwisted (ie, substantially parallel or parallel) glass filaments bonded (when forming glass filaments) into a single strand and wound onto a bobbin.

[0054] Any suitable glass reinforcing fiber may be used as the first fiber or the second fiber. For example, E glass, E-CR glass (such as Advantex available from Owens Corning) may be used. TM Glass fibers), fibers made of C-glass, H-glass, S-glass, and AR glass types.

[0055] In an embodiment, the linear mass density of the glass fibers referred to herein (e.g., the first fibers that may be glass fibers and / or the second fibers that may be glass fibers) ranges from about 50 tex to about 5000 tex, for example, from about 200 tex to about 4800 tex, from about 300 tex to about 2500 tex, from about 300 tex to about 2400 tex, or from about 600 tex to about 1200 tex.

[0056] The term "carbon fiber" is used herein to refer to a plurality of continuous carbon filaments (the term "continuous" as used herein is used to refer to a fiber / filament having a length many times longer than its diameter, for example at least about 5000 times longer than its diameter, for example about 10 000 times longer than its diameter). The carbon fibers used in the fabrics described herein can be provided as carbon fiber tows (or strands), which are bundles of continuous carbon filaments. The carbon fibers described herein (e.g., the carbon fibers of the first fibers and / or the second fibers) may include a sizing agent on their surface, such as a sizing agent applied to the carbon fibers during fiber formation. The sizing agent may include components that promote the formation of carbon fibers and / or their use in a matrix resin, such as a film former, a lubricant, a coupling agent (to promote compatibility between carbon fibers and a resin used to form a composite product comprising a hybrid fabric described herein), etc. In some embodiments, the carbon fibers include a polyester compatible sizing agent or an epoxy compatible sizing agent.

[0057] In an embodiment, the linear mass density of the carbon fibers ranges from about 100 tex to about 5000 tex, e.g., from about 200 tex to about 5000 tex, from about 400 tex to about 5000 tex, from about 600 tex to about 5000 tex, from about 800 tex to about 5000 tex, from about 100 tex to about 4800 tex, from about 200 tex to about 4800 tex, from about 400 tex to about 4800 tex, from about 600 tex to about 4000 tex, tex, about 800 tex to about 4800 tex, about 100 tex to about 2400 tex, about 200 tex to about 2400 tex, about 400 tex to about 2400 tex, about 100 tex to about 2000 tex, about 200 tex to about 2000 tex, about 400 tex to about 2000 tex, about 600 tex to about 2000 tex, about 800 tex to about 2000 tex, or about 1200 tex.

[0058] In an embodiment, the carbon fiber (when present) is provided by a carbon fiber tow (carbon fiber strand). In an embodiment, the size of the carbon fiber tow ranges from 6K to 50K, such as 6K to 24K or 6K to 12K. For example, the first fiber can be fed from one or more carbon fiber tows ranging in size from 6K to 50K, such as 6K to 24K or 6K to 12K. The designation #K means that the carbon tow consists of #×1,000 individual carbon filaments, i.e., a carbon fiber tow of size 6K consists of approximately 6000 carbon fiber filaments / fibers.

[0059] In an embodiment, the fabric is a non-crimped fabric, and the first fiber and the second fiber utilize stitching yarn to remain on their corresponding orientation (rather than the first fiber and the second fiber are woven together, i.e., the non-crimped fabric is a non-woven fabric). Any suitable stitching yarn can be adopted. In an embodiment, the stitching yarn is a polyester yarn. In an embodiment, the linear mass density range of the stitching yarn is from about 50 dtex to about 300 dtex. In an embodiment, the stitching yarn passes through fabric to form a stitching pattern, and this stitching pattern can be selected from tricot stitching pattern, symmetrical double tricot stitching pattern, asymmetrical double tricot stitching pattern, symmetrical stitching pattern and asymmetrical stitching pattern. In an embodiment, the stitching yarn passes through fabric to form a stitching pattern, and this stitching pattern is a tricot stitching pattern. In an embodiment, the stitching yarn limits a stitching length, and the scope of this stitching length is from about 2mm to about 7mm, for example, about 3mm.

[0060] In an embodiment, the fiber fabric is a woven fabric, such as a plain woven fabric, a warp knit fabric, or a twill woven fabric.

[0061] In an embodiment, the fiber fabric consists essentially of or consists of glass fibers and / or carbon fibers. In an embodiment, the fiber fabric consists essentially of or consists of glass fibers and carbon fibers. In an embodiment, the fiber fabric consists essentially of or consists of glass fibers.

[0062] In an embodiment, the fiber fabric comprises glass fibers. In an embodiment, the fiber fabric comprises additional fibers in addition to the glass fibers. In an embodiment, the fiber fabric comprises additional fibers in addition to the glass fibers and / or carbon fibers. Examples of other fibers that may be included in the fiber fabric include polymer fibers, such as PET.

[0063] In an embodiment, the fiber fabric has a weight per unit area in the range of about 200 g / m 2 About 2500g / m 2 , for example about 300g / m 2 About 2000g / m 2 , for example, about 500 g / m 2About 1500g / m 2 , for example, about 500 g / m 2 About 1300g / m 2 The weight per unit area of ​​a fabric can be determined according to ISO 3374.

[0064] In an embodiment, the fiber fabric comprises:

[0065] first fibers oriented in a first direction; and

[0066] second fibers oriented in a second direction,

[0067] Wherein the first fibers comprise glass fibers, the second fibers comprise glass fibers, the second direction is within 45 degrees to 90 degrees of the first direction, and the first fibers and the second fibers are maintained in their respective orientations by the stitching yarn.

[0068] In an embodiment, the fiber fabric comprises:

[0069] first fibers oriented in a first direction; and

[0070] second fibers oriented in a second direction,

[0071] The first fibers include glass fibers, the second fibers include glass fibers, the second direction is within 45 to 90 degrees of the first direction, the first fibers and the second fibers are maintained in their respective orientations by stitching yarns, and the glass fibers of the first fibers and / or the second fibers contain a polyester compatible sizing agent or an epoxy resin compatible sizing agent.

[0072] In an embodiment, the fiber fabric comprises:

[0073] first fibers oriented in a first direction; and

[0074] second fibers oriented in a second direction,

[0075] The first fibers include glass fibers, the second fibers include glass fibers, the second direction is within 45 degrees to 90 degrees of the first direction, the first fibers and the second fibers are maintained in their respective orientations by stitching yarns, the glass fibers of the first fibers and / or the second fibers contain a polyester compatible sizing agent or an epoxy resin compatible sizing agent, and the fiber fabric has a weight per unit area in the range of about 500 g / m 2 About 2500g / m 2 .

[0076] Binder

[0077] Functionalized fabrics include a binder. The binder can be in the form of binder particles. Functionalized fabrics can be described herein as including binder particles. Functionalized fabrics can be described herein as comprising a fiber fabric having binder particles adhered to the fiber fabric surface.

[0078] The binder (e.g., binder particles) comprises, consists of, or consists essentially of a fluorescent material. The binder and fluorescent material may together comprise one or more than one type of material. The fluorescent material may be one or more than one fluorescent material. The binder fluoresces in response to incident electromagnetic radiation (i.e., light). The fluorescent material or more than one fluorescent material may be a UV fluorescent material, which is considered to mean that the material fluoresces when exposed to UV light.

[0079] UV light radiates at a shorter wavelength than visible light. When absorbed by the fluorescent material, the UV light is reflected back to the observer as visible light of a longer wavelength. The color of the observed fluorescence will depend on the materials used and the wavelength of the light. For example, a UV source with an appropriate wavelength can be used in combination with a given UV fluorescent material.

[0080] Fluorescence and fluorescent materials generally refer to any material, pigment, compound or agent that absorbs certain frequencies of electromagnetic radiation (i.e., light) and re-emits the electromagnetic radiation at a lower frequency, such that a fabric on which the fluorescent material is present appears to glow when exposed to the lower frequency of electromagnetic radiation (i.e., light). References to fluorescent materials will be deemed to include references to phosphorescent materials. Incident radiation may be referred to as having an excitation wavelength. The excitation wavelength is understood to be electromagnetic radiation including a wavelength that causes the fluorescent material to glow. Typically, the excitation wavelength corresponds to the excitation wavelength of UV light or visible light.

[0081] The presence of fluorescent material makes the adhesive emit light when radiation of suitable wavelength is incident on the adhesive. The wavelength of incident radiation can correspond to the wavelength of visible light or UV light. Visible light is generally considered to be in the range of about 380nm to about 750nm. UV light is generally considered to be in the range of about 10nm to about 400nm. The use of UV fluorescent material is preferred because it may not be necessary for the adhesive to emit light under typical daily lighting conditions. Regarding the use of UV light, the wavelength of incident UV light or radiation can be about 10nm to about 400nm, for example, about 100nm to about 400nm, or about 200nm to about 400nm, or about 300nm to about 400nm, or about 250nm to about 380nm. Typical specific examples are about 254nm or about 365nm.

[0082] The source of electromagnetic radiation may be provided by any suitable radiation source known to the skilled person.

[0083] The fluorescent material may be selected from any known fluorescent material. The fluorescent material may be a polymer or a material other than a polymer. In an embodiment, the binder comprises a fluorescent resin (eg, a fluorescent polyester resin) or consists of a fluorescent resin.

[0084] In the functionalized fabric, the fluorescent material may be present in an amount of up to about 5 wt %, for example, up to about 4.5 wt %, up to about 4.0 wt %, or up to about 3.5 wt % of the functionalized fabric, based on the total weight of the functionalized fabric. In an embodiment, the fluorescent material may account for at least about 0.05 wt % of the functionalized fabric, for example, at least about 0.1 wt %, at least about 0.2 wt %, or at least about 0.3 wt % of the functionalized fabric. In an embodiment, the fluorescent material accounts for about 0.05 wt % to about 5.0 wt % of the functionalized fabric, for example, about 0.1 wt % to about 3.5 wt % of the functionalized fabric.

[0085] In an embodiment, the functionalized fabric comprises up to about 30 g / m 2 of fluorescent material, for example, up to about 25 g / m 2 , up to about 20g / m 2 , up to about 18g / m 2 , up to about 16g / m 2 , up to about 15g / m 2 or up to about 13g / m 2 In an embodiment, the functionalized fabric comprises at least about 2 g / m 2 of fluorescent material, for example at least about 4 g / m 2 , at least about 5g / m 2 , at least about 7g / m 2 , at least about 8g / m 2 or at least about 10g / m 2 In an embodiment, the functionalized fabric comprises about 2 g / m 2 About 30g / m 2 of fluorescent material, for example, about 4 g / m 2 About 25g / m 2 , about 4g / m 2 About 15g / m 2 , about 7g / m 2 About 13g / m 2 or about 10g / m 2 About 13g / m 2 of fluorescent materials.

[0086] In an embodiment, the binder (e.g., binder particles) includes a resin binder, is substantially composed of a resin binder, or is composed of a resin binder. In an embodiment, the binder (e.g., binder particles) includes a thermoplastic resin or is composed of a thermoplastic resin. In an embodiment, the binder (e.g., binder particles) includes a thermoplastic resin or is composed of a thermoplastic resin, and the thermoplastic resin is selected from epoxy resins, acrylate resins, or polyester resins. In an embodiment, the binder (e.g., binder particles) includes a thermoplastic resin or is composed of a thermoplastic resin, and the thermoplastic resin is selected from epoxy resins or polyester resins. In an embodiment, the binder (e.g., binder particles) includes a resin containing epoxy, acrylate, or ester functional groups or is composed of the resin, and the resin is, for example, a resin containing epoxy or ester functional groups. In an embodiment, the binder (e.g., binder particles) includes a bio-based resin or is composed of a bio-based resin, and the bio-based resin is, for example, a bio-based resin containing epoxy, acrylate, or ester functional groups. The resin or thermoplastic resin itself can provide fluorescent properties or is a fluorescent material. Fluorescent properties may be provided by materials other than resins or thermoplastic resins. Thus, the fluorescent material may be any material described herein as a binder particle. For example, the fluorescent material may be selected from one or more fluorescent polymer resins, including those mentioned herein, such as saturated or unsaturated polyester resins, or epoxy resins. Other suitable fluorescent polymer resins include one or more polyacrylates or acylate functionalized polymers.

[0087] In an embodiment, the glass transition temperature of the binder (e.g., binder particles) is at most about 75°C, such as at most about 70°C, at most about 65°C, at most about 60°C, or at most about 55°C. In an embodiment, the glass transition temperature of the binder is at least about 30°C, such as at least about 35°C or at least about 40°C. In an embodiment, the glass transition temperature of the binder (e.g., binder particles) ranges from about 30°C to about 75°C, such as about 40°C to about 70°C. The glass transition temperature of the binder can be determined using differential scanning calorimetry (DSC) according to EN ISO 11357-2 (determination of glass transition temperature). The glass transition temperature of the binder can be determined using differential scanning calorimetry (DSC) according to EN ISO 11357-2 (determination of glass transition temperature), wherein the glass transition temperature is determined as the value provided by the second heating cycle. The glass transition temperature of the binder can be determined according to the EN ISO 11357-2 test method by heating the binder at a heating rate of 10K / min at an air flow rate of 80mL / min, from -60°C to 120°C. In an embodiment, the glass transition temperature of the binder can be determined according to the EN ISO 11357-2 test method by heating the binder at a heating rate of 10K / min at an air flow rate of 80mL / min, from -60°C to 120°C, then holding at 120°C for 5 minutes, then cooling from 120°C to -60°C at a cooling rate of 10K / min, then holding at -60°C for 5 minutes, then heating again from -60°C to 120°C at a heating rate of 10K / min, and the glass transition temperature is determined as the value provided by the second heating cycle.

[0088] In an embodiment, the binder (e.g., binder particles) has a melting point such that the binder is completely melted when exposed to a temperature of at most about 120°C for at least a suitable period of time, such as when exposed to a temperature of at most about 110°C for at least a suitable period of time, when exposed to a temperature of at most about 100°C for at least a suitable period of time, or when exposed to a temperature of at most about 90°C for at least a suitable period of time. In an embodiment, the binder has a melting point such that the binder is completely melted when exposed to a temperature ranging from about 60°C to about 120°C, such as from about 80°C to about 120°C for at least a suitable period of time. A suitable period of time may be at most 1 hour, such as at most 30 minutes. A suitable period of time may be at least about 1 minute, such as at least about 5 minutes or at least about 10 minutes.

[0089] In an embodiment, the softening temperature of the binder (e.g., binder particles) ranges from about 50° C. to about 100° C., such as about 60° C. to about 100° C. In an embodiment, the softening temperature can be measured with a binder sample having a thickness of 400 μm and a diameter of 25 mm, using an oscillatory rheometer at 0.1% deformation in a plane-plane geometry, a frequency of 1 Hz, using a heating-cooling-heating cycle, the cycle heating from 30° C. to 130° C. at a rate of 3° C. / min, cooling from 130° C. to 30° C. at a rate of 3° C. / min, and heating from 30° C. to 130° C. The softening temperature is measured during the first heating.

[0090] In an embodiment, the binder is applied to the fiber fabric as binder particles. Before being applied to the fiber fabric, the volume average particle size of the binder particles may be at most about 1 mm, for example, at most about 800 μm, at most about 600 μm, at most about 500 μm, at most about 400 μm, at most about 300 μm, or at most about 200 μm. In an embodiment, before being applied to the fiber fabric, the volume average particle size of the binder particles is greater than about 10 μm, for example, greater than about 20 μm, greater than about 30 μm, greater than about 40 μm, or greater than about 50 μm. In an embodiment, before being applied to the fiber fabric, the volume average particle size of the binder particles ranges from about 10 μm to about 1 mm, for example, from about 20 μm to about 600 μm, from about 30 μm to about 500 μm, from about 40 μm to about 400 μm, or from about 50 μm to about 300 μm. Dynamic light scattering techniques can be used on a dispersion of binder particles to determine the volume average particle size of the binder particles prior to application to the fiber fabric. A particle size analyzer (such as available from Beckman TM The volume average particle size was determined by laser diffraction (i.e., using dynamic light scattering technology on a dispersion of binder particles) according to ISO 13320 2009. After the sample was dispersed in air, it was analyzed twice as is, and the sample amount for each test was generally about 20 g.

[0091] In embodiments, the binder of the functionalized fabric may be described as binder particles.

[0092] In an embodiment, the binder particles applied to the fiber fabric may adhere to the surface of the fiber fabric so that the functionalized fabric comprises the binder particles adhered to the surface. In an embodiment, the binder particles applied to the surface of the fiber fabric may adhere to the fiber fabric to form a functionalized fabric.

[0093] In an embodiment, based on the total weight of the functionalized fabric, the binder (comprising a fluorescent material, consisting essentially of a fluorescent material, or consisting of a fluorescent material) may be present in an amount of up to about 5% by weight. In such embodiments, due to the small amount of binder particles applied to the fiber fabric as described herein, the functionalized fabric includes a fiber fabric having binder particles adhered to the fiber fabric, and the binder particles form independent binder particles on the surface of the fiber fabric (e.g., rather than the binder condensing on the surface of the fiber fabric to form a large mass or layer). The terms "independent binder particles" and "discrete binder particles" are used herein to refer to the binder particles adhered to the surface of the fiber fabric being spaced apart from each other, i.e., there is a fiber fabric surface area free of binder particles around each binder particle. In an embodiment, the longest axial length of the binder particles adhered to the surface of the fiber fabric is less than about 2 mm, for example, less than about 1 mm.

[0094] In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least about 90% by weight of the binder particles attached to the fiber fabric surface have a longest axial length of less than about 2 mm, such as less than about 1 mm, less than about 800 μm, less than about 700 μm, less than about 600 μm, or less than about 500 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that the longest axial length of the binder particles attached to the fiber fabric surface is at least about 1 μm, at least about 10 μm, or at least about 20 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least about 90% by weight of the binder particles attached to the fiber fabric surface have a longest axial length of at least about 1 μm, at least about 10 μm, or at least about 20 μm.

[0095] In embodiments, the binder particles attached to the functionalized fabric surface have a particle size distribution such that the longest axial length of the binder particles attached to the fiber fabric surface is in the range of about 1 μm to about 1 mm, such as in the range of about 1 μm to about 800 μm.

[0096] In an embodiment, the binder particles adhered to the surface of the functionalized fabric have a particle size distribution such that at least about 90% by weight of the binder particles adhered to the surface of the fiber fabric have a longest axial length in the range of about 1 μm to about 1 mm, such as in the range of about 1 μm to about 800 μm, about 10 μm to about 600 μm, or about 10 μm to about 500 μm.

[0097] In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles (by number of particles) attached to the fiber fabric surface have a longest axial length of less than about 2 mm, for example, less than about 1 mm, less than about 800 μm, less than about 700 μm, less than about 600 μm, or less than about 500 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles (by number of particles) attached to the fiber fabric surface have a longest axial length of at least about 1 μm, at least about 10 μm, or at least about 20 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles (by number of particles) attached to the fiber fabric surface have a longest axial length in the range of about 1 μm to about 1 mm, for example, in the range of about 1 μm to about 800 μm, about 10 μm to about 600 μm, or about 10 μm to about 500 μm.

[0098] The longest axial length of the binder particles of the functionalized fabric can be determined by measuring the maximum lateral dimension of the binder particles adhered to the fiber fabric. An optical microscope (such as Keyence TM An optical microscope (such as Keyence TM Optical microscope, such as Keyence TM VHX-500) and associated image analysis software (e.g., ImageJ software) to determine the binder particle size distribution. An optical microscope and associated image analysis software (e.g., as described herein) can be used to calculate the particle size distribution of a given functionalized fabric area (e.g., about 5 mm 2 To about 50mm 2 The functionalized fabric area is within the range of about 5 mm 2 To about 20mm 2 Functionalized fabric area within the range of about 5mm 2 To about 10mm 2 The binder particle size distribution can be determined by measuring the binder particle size distribution on the functionalized fabric area within a range of 5 mm. In an embodiment, an optical microscope and related image analysis software (e.g., as described herein) can be used to calculate the 5 mm 2 or 10mm 2 The binder particle size distribution over the functionalized fabric area is determined.

[0099] In embodiments, the binder of the functionalized fabric can be described as binder particles having a shape that can be detected using a numerical aperture microscope (e.g., Keyence TMVHX-500) and associated image analysis software to determine the volume average particle size (i.e., after application and adhesion / fixation (e.g., by melting) to the fiber fabric) (e.g., the particle size of each particle can be determined as the largest transverse dimension of the particle, i.e., the longest axial length of the particle adhered to the fabric surface). In an embodiment, after application and adhesion / fixation to the fiber fabric, the volume average particle size of the binder particles ranges from about 10 μm to about 1 mm, such as from about 20 μm to about 600 μm, from about 30 μm to about 500 μm.

[0100] In an embodiment, the binder of the functionalized fabric can be described as binder particles, and before being applied to the fiber fabric, the binder particles have a D90 particle size of less than (i.e., 90% by volume of the particles have a particle size less than) about 1 mm, such as less than about 800 μm, less than about 600 μm, less than about 500 μm, less than about 400 μm, less than about 300 μm, or less than about 200 μm. The D90 particle size (by volume) can be determined by sieve analysis according to ISO 8130-1.

[0101] In an embodiment, the shear modulus G of the binder (e.g., binder particles) at 30° C. ranges from about 5 MPa to about 50 MPa, such as from about 5 MPa to about 40 MPa, or from about 7 MPa to about 30 MPa. The shear modulus G of the binder at 30° C. can be measured using an oscillatory rheometer at a frequency of 1 Hz and 0.1% deformation in a plane-plane geometry with a heating-cooling-heating cycle of heating from 30° C. to 130° C. at a rate of 3° C. / min, cooling from 130° C. to 30° C. at a rate of 3° C. / min, and heating from 30° C. to 130° C.

[0102] In an embodiment, the dynamic viscosity η of the binder (e.g., binder particles) at 130° C. ranges from about 1 Pa.s to about 400 Pa.s, such as from about 10 Pa.s to about 400 Pa.s. The dynamic viscosity η of the binder at 130° C. can be measured using an oscillatory rheometer at a frequency of 1 Hz and 0.1% deformation in a plane-plane geometry with a heating-cooling-heating cycle of heating from 30° C. to 130° C. at a rate of 3° C. / min, cooling from 130° C. to 30° C. at a rate of 3° C. / min, and heating from 30° C. to 130° C. from 30° C. to 130° C.

[0103] In an embodiment, the binder (e.g., binder particles) comprises or is composed of a resin containing an epoxy functional group, for example, the binder may be an epoxy resin. In an embodiment, the binder comprises or is composed of an epoxy resin, the molecular weight Mw of which ranges from about 2000 to about 6000, for example, from about 3000 to about 6000, from about 4000 to about 6000, or from about 4500 to about 5500. In an embodiment, the binder comprises or is composed of an epoxy resin, the molecular weight Mw of which ranges from about 2000 to about 6000, and the polydispersity ranges from 1 to 5, for example, from 2 to 4, from 2 to 3, or from 2.5 to 3 (wherein the polydispersity is calculated by Mw / Mn). In an embodiment, the binder comprises or is composed of an epoxy resin, and the epoxy resin is epoxidized BPA or epoxy phenolic resin. In an embodiment, the binder comprises or is composed of an epoxy resin, and the epoxy resin is epoxidized BPA.

[0104] In an embodiment, the binder (e.g., binder particles) comprises a resin containing an ester functional group or is composed of the resin, for example, the binder can be a polyester resin. In an embodiment, the binder comprises a polyester resin or is composed of a polyester resin, the molecular weight MW of which ranges from about 1000 to about 300000. In an embodiment, the binder comprises an unsaturated polyester resin or is composed of an unsaturated polyester resin, for example, an aromatic unsaturated polyester resin or an aliphatic unsaturated polyester resin. The example of a suitable polyester-based resin includes a BPA polyester such as a BPA fumarate polyester, for example an alkoxylated (e.g., ethoxylated or propoxylated) BPA fumarate polyester.

[0105] In an embodiment, the binder of the functionalized fabric is disposed on the surface of the fiber fabric. In an embodiment, the binder particles of the functionalized fabric are disposed on the surface of the fiber fabric. In an embodiment, at least some of the binder of the functionalized fabric is present on the surface of the functionalized fabric. For example, at least some of the binder of the functionalized fabric is disposed on the surface of the fiber fabric or between fibers on the surface of the fiber fabric.

[0106] In an embodiment, a majority of the binder (e.g., binder particles) of the functionalized fabric is disposed on a surface of the fiber fabric. For example, in an embodiment, at least 50% by weight (e.g., at least about 60% by weight, at least about 75% by weight, at least about 85% by weight, or at least about 90% by weight) of the binder of the functionalized fabric is disposed on one surface of the fiber fabric.

[0107] In embodiments, the binder of the functionalized fabric may be applied to the fiber fabric in the form of binder particles (which may also be described as powdered binder particles), a dispersion comprising the binder, or a solution comprising the binder.

[0108] In an embodiment, the binder of the functionalized fabric may permeate the fiber fabric. In an embodiment, the functionalized fabric may contain the binder within the fiber fabric.

[0109] In an embodiment, when present on a functionalized fabric, the binder particles do not cover or coat or impregnate the entire surface of the fabric. For any given surface on which the binder particles are present, there may be one or more gaps within the extent to which the functionalized fabric is covered by the binder particles. For any given surface on which the binder particles are present, there may be discrete areas or isolated portions of the binder particles.

[0110] Functional fabrics

[0111] The functionalized fabric of the present invention comprises a fiber fabric as described herein and a binder (eg, binder particles) as described herein.

[0112] Binder (e.g., binder particles) may account for up to about 5% by weight of the functionalized fabric. In embodiments, the binder accounts for up to about 5.0% by weight of the functionalized fabric, such as up to about 4.5% by weight, up to about 4.0% by weight, or up to about 3.5% by weight of the functionalized fabric. In embodiments, the binder accounts for at least about 0.1% by weight of the functionalized fabric, such as at least about 0.2% by weight or at least about 0.3% by weight of the functionalized fabric. In embodiments, the binder accounts for about 0.1% to about 5.0% by weight of the functionalized fabric, such as about 0.1% to about 4.0% by weight, or about 0.2% to about 3.5% by weight of the functionalized fabric.

[0113] In embodiments, the glass fibers comprise at least about 50% by weight of the functionalized fabric, e.g., at least about 60% by weight of the functionalized fabric, at least about 70% by weight of the functionalized fabric, at least about 80% by weight of the functionalized fabric, or at least about 90% by weight of the functionalized fabric.

[0114] In an embodiment, the functionalized fabric comprises up to about 30 g / m 2 of a binder (e.g., binder particles), e.g., up to about 25 g / m 2 , up to about 20g / m 2 , up to about 18g / m 2 , up to about 16g / m 2 , up to about 15g / m 2 or up to about 13g / m 2 In an embodiment, the functionalized fabric comprises at least about 2 g / m 2 of adhesive, for example at least about 4 g / m 2 , at least about 5g / m 2 , at least about 7g / m2 , at least about 8g / m 2 or at least about 10g / m 2 In an embodiment, the functionalized fabric comprises about 2 g / m 2 About 30g / m 2 of adhesive, for example about 4 g / m 2 About 25g / m 2 , about 4g / m 2 About 15g / m 2 , about 7g / m 2 About 13g / m 2 or about 10g / m 2 About 13g / m 2 of adhesive.

[0115] In an embodiment, the functionalized fabric comprises a binder (e.g., binder particles) disposed on a surface of a fiber fabric. The fiber fabric may be described as a generally two-dimensional fabric having a top surface and a bottom surface. In an embodiment, the functionalized fabric may comprise a fiber fabric having one surface having a binder disposed thereon and another surface substantially free of the binder (e.g., comprising less than about 0.1 g / m 2 surface of the adhesive).

[0116] In embodiments, the functionalized fabric may include a binder (eg, binder particles) within the fiber fabric.

[0117] Functionalized fabrics include fabrics and binders, which adhere to the fabrics. In an embodiment, the binder adheres to the fabrics, such as the surface of the fabrics. In an embodiment, the binder can be adhered to the fabrics by suitable treatment (such as heating, curing or exposure to UV radiation). In an embodiment, the binder adheres to the fabrics, such as the surface of the fabrics, by heating so that the binder melts or melts at least partially, such as at least partially melts on the surface of the fabrics. For example, the functionalized fabric may include a solid binder (such as solid binder particles) that adheres to the fabrics, wherein the binder (such as binder particles) applied to the fabrics has been softened or at least partially melted before. The inventors have found that, since the amount of binder applied to the fabrics is less, even after the melted binder, discrete regions of the binder (which may be referred to as binder particles or independent binder particles) will be provided in the functionalized fabrics (such as on the surface of the functionalized fabrics). Figure 23D microscopic images of examples of functionalized fabrics as described herein, it can be seen that the binder particles applied to the surface of the fiber fabric and then melted and solidified do not condense to form a layer on the surface of the fabric, but can be seen as independent binder particles. The term "independent binder particles" or "discrete binder particles" can be used herein to describe binder particles that adhere to the fiber fabric and have a particle size distribution as described herein. As described above, the terms "independent binder particles" and "discrete binder particles" are used herein to refer to the binder particles that adhere to the surface of the fiber fabric being spaced apart from each other, that is, there is a fiber fabric surface area that does not contain binder particles around each binder particle.

[0118] In an embodiment, the functionalized fabrics described herein can be described as comprising a fiber fabric having a surface to which a binder (e.g., binder particles) is permanently adhered. The term "permanently adhered" is used herein to refer to a binder (e.g., binder particles) that cannot be removed from a fiber fabric by abrasion (e.g., abrasion testing as described in the Examples section below). The binder (e.g., binder particles) can be permanently adhered to the surface of a fiber fabric by softening or at least partially melting the binder on the surface of a fiber fabric as described herein. For example, if a microfiber fabric or Scotch-Brite is used in the absence of a liquid according to ISO 11998-2006 (using an Elcometer 1720 abrasion tester), the binder particles can be permanently adhered to the surface of the fiber fabric. TM After scrubbing tests with the 7446 pad as the abrasive pad (weight of the abrasive pad with stand 455 g, 300 mm long scrubbing surface, 200 runs (back and forth)), no effect on the adhesive adhesion was observed and no weight loss occurred, the adhesive was considered to be permanently adhered to the surface of the fiber fabric.

[0119] In an embodiment, at least about 80% by weight of the binder (e.g., binder particles) is disposed on one surface of the fiber fabric of the functionalized fabric, such as at least about 85%, at least about 90%, or at least about 95% by weight of the binder (e.g., binder particles) is disposed on one surface of the fiber fabric of the functionalized fabric. For example, the functionalized fabric may include a fiber fabric having a first surface and a second surface, the first surface having at least about 80% by weight (e.g., at least about 90% by weight or at least about 95% by weight) of the binder (e.g., binder particles) disposed thereon, and the second surface having substantially no binder (e.g., less than 5% by weight of the binder (e.g., binder particles) disposed thereon on the second surface of the fiber fabric, such as less than 3% by weight, less than 2% by weight, less than 1% by weight, or less than 0.5% by weight of the binder (e.g., binder particles) disposed thereon on the second surface of the fiber fabric.

[0120] In an embodiment, the functionalized fabric comprises binder particles adhered to the surface of the fiber fabric. For example, the functionalized fabric may comprise solid binder particles adhered to the fiber fabric, wherein the binder particles have previously been softened or at least partially melted on the surface of the fiber fabric.

[0121] In embodiments, the functionalized fabrics described herein may be impregnated with a resin and the resin cured to form a composite article.

[0122] Fabric Lamination

[0123] The fabric laminate comprises at least two layers of functionalized fabric as described herein.

[0124] In an embodiment, the fabric laminate comprises at least two layers of fabric as described herein, wherein one layer of functionalized fabric is directly disposed on another layer of functionalized fabric. In an embodiment, the fabric laminate comprises at least 3 layers of functionalized fabric as described herein, for example at least 4 layers, at least 6 layers or at least 8 layers of functionalized fabric as described herein. In an embodiment, the fabric laminate comprises up to 50 layers of functionalized fabric as described herein, for example up to 30 layers, up to 25 layers, up to 20 layers, up to 15 layers, up to 10 layers of functionalized fabric as described herein. In an embodiment, the fabric laminate comprises 2 to 50 layers of functionalized fabric as described herein, for example 4 to 30 layers or 6 to 25 layers of functionalized fabric as described herein. In an embodiment, the fabric laminate comprises multiple layers of functionalized fabric as described herein, wherein each layer of the multiple layers of functionalized fabric is directly disposed on another layer of the multiple layers of functionalized fabric.

[0125] In an embodiment, the fabric stack includes multiple layers of functionalized fabrics as described herein, each layer of the multiple layers of functionalized fabrics is directly disposed on another layer of the multiple layers of functionalized fabrics, each layer of the multiple layers of functionalized fabrics has one surface on which a binder (e.g., binder particles) is disposed and another surface that is substantially free of binder, wherein each functionalized fabric in the multiple functionalized fabrics is stacked so that the surface of each functionalized fabric in the multiple functionalized fabrics on which the binder is disposed is directly disposed on the surface of another layer of the multiple layers of functionalized fabrics that is substantially free of binder.

[0126] In an embodiment, the layers of the fabric laminate are adhered to each other. A fabric laminate in which the layers of the fabric laminate are adhered to each other may be referred to herein as a "consolidated fabric laminate".

[0127] In an embodiment, the layers of the fabric laminate may be adhered to each other by a suitable treatment, such as heating, curing, or exposure to UV radiation. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate so that the binder particles of the first layer of functionalized fabric adhere the first layer of functionalized fabric to the second layer of functionalized fabric. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature higher than the glass transition temperature of the binder, such as heating to a temperature at least about 5°C higher than the glass transition temperature of the binder, heating to a temperature at least about 10°C higher than the glass transition temperature of the binder, or heating to a temperature at least about 15°C higher than the glass transition temperature of the binder. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature higher than the softening temperature of the binder, such as heating to a temperature at least about 5°C higher than the softening temperature, heating to a temperature at least about 10°C higher than the softening temperature, or heating to a temperature at least about 15°C higher than the softening temperature. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature higher than the melting temperature of the binder. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature of at least about 50°C, such as at least about 60°C, at least about 70°C, at least about 80°C, at least about 90°C, or at least about 100°C. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature of up to about 150°C, such as up to about 130°C or up to about 120°C. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature ranging from about 50°C to about 150°C, such as from about 70°C to about 130°C or from about 80°C to about 120°C. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate as described above for about 1 minute or more, such as up to about 1 hour, such as from about 1 minute to about 10 minutes.

[0128] In an embodiment, providing a consolidated fabric laminate may include adhering the layers of the fabric laminate to each other. In an embodiment, the layers of the fabric laminate may be adhered to each other by exposing the fabric laminate to a temperature of up to about 150° C. and a pressure below atmospheric pressure, such as a pressure in the range of about 500 mbar to about 1000 mbar, or about 600 mbar to about 1000 mbar, about 700 mbar to about 1000 mbar, about 750 mbar to about 1000 mbar, about 800 mbar to about 1000 mbar, or about 900 mbar. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of up to about 5 hours, such as up to about 3 hours, up to about 2 hours, or up to about 1 hour, to form a consolidated fabric laminate. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of at least about 10 minutes, such as at least about 30 minutes, to form a consolidated fabric laminate. In embodiments, the fabric laminate is exposed to elevated temperature (i.e., heat) and / or reduced pressure for a period of about 10 minutes to about 5 hours, e.g., about 30 minutes to about 2 hours or about 30 minutes to about 1 hour, to form a consolidated fabric laminate.

[0129] In embodiments, a fabric layup or consolidated fabric layup described herein may be impregnated with a resin and the resin cured to form a composite article.

[0130] Method for producing functionalized fabrics

[0131] Methods for producing functionalized fabrics may include:

[0132] Providing a fiber fabric as described herein; and

[0133] A binder (eg, binder particles) as described herein is applied to a fibrous fabric to provide a functionalized fabric.

[0134] The binder may be applied to the fibrous web in an amount such that the binder comprises up to about 5% by weight of the functionalized web.

[0135] In an embodiment, the method includes applying a binder (e.g., binder particles) to the fiber web to provide a binder particle distribution of up to about 30 g / m 2 , for example up to about 20 g / m 2 , up to about 25g / m 2 , up to about 18g / m 2 , up to about 16g / m 2 , up to about 15g / m 2 or up to about 13g / m 2 In an embodiment, the method includes applying a binder to the fiber fabric to provide a binder particle distribution of at least about 2 g / m2 , for example at least about 4 g / m 2 , at least about 5g / m 2 , at least about 7g / m 2 , at least about 8g / m 2 or at least about 10g / m 2 In an embodiment, the method includes applying a binder to the fiber fabric to provide a binder particle distribution range of about 2 g / m 2 About 30g / m 2 , for example about 4g / m 2 About 20g / m 2 , about 4g / m 2 About 15g / m 2 , about 7g / m 2 About 13g / m 2 or about 10g / m 2 About 13g / m 2 functionalized fabrics.

[0136] In an embodiment, the binder is applied to the surface of the fiber fabric, for example, by spreading binder particles over the surface of the fiber fabric.

[0137] In an embodiment, the binder is applied to the surface of the fiber fabric as binder particles. The volume average particle size of the binder particles applied to the fiber fabric may be at most about 1 mm, for example, at most about 800 μm, at most about 600 μm, at most about 500 μm, at most about 400 μm, at most about 300 μm, or at most about 200 μm. In an embodiment, the volume average particle size of the binder particles applied to the fiber fabric is greater than about 10 μm, for example, greater than about 20 μm, greater than about 30 μm, greater than about 40 μm, or greater than about 50 μm. In an embodiment, the volume average particle size range of the binder particles applied to the fiber fabric is from about 10 μm to about 1 mm, for example, from about 20 μm to about 600 μm, from about 30 μm to about 500 μm, from about 40 μm to about 400 μm, or from about 50 μm to about 300 μm. The volume average particle size of the binder particles applied to the fiber fabric can be determined using a dynamic light scattering technique on a dispersion of the binder particles prior to application to the fiber fabric. A particle size analyzer (such as available from Beckman TM The volume average particle size is determined by laser diffraction (i.e., using dynamic light scattering techniques on a dispersion of binder particles before application to the fiber fabric) using a LS13320 particle size analyzer from Sigma-Aldrich (Shanghai) in accordance with ISO 13320 2009. The sample can be analyzed twice as is after dispersion in air, and the sample amount for each test is typically about 20 g.

[0138] In an embodiment, the binder (e.g., binder particles) may be adhered to the fiber fabric by a suitable treatment such as heating, curing, or exposure to UV radiation. In an embodiment, the method comprises heating the functionalized fabric to adhere the binder to the fiber fabric. In an embodiment, the method comprises heating the binder to adhere the binder to the fiber fabric. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature higher than the glass transition temperature of the binder, for example, heating to a temperature at least about 5°C higher than the glass transition temperature of the binder, heating to a temperature at least about 10°C higher than the glass transition temperature of the binder, or heating to a temperature at least about 15°C higher than the glass transition temperature of the binder. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature higher than the softening temperature of the binder, for example, heating to a temperature at least about 5°C higher than the softening temperature, heating to a temperature at least about 10°C higher than the softening temperature, or heating to a temperature at least about 15°C higher than the softening temperature. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature higher than the melting temperature of the binder. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature of at least about 50°C, such as at least about 60°C, at least about 70°C, at least about 80°C, at least about 90°C, or at least about 100°C. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature of up to about 150°C, such as up to about 130°C or up to about 120°C. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature in the range of about 50°C to about 150°C, such as about 70°C to about 130°C or about 80°C to about 120°C. In embodiments, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric as described above for about 1 minute or more, such as up to about 1 hour, such as about 1 minute to about 10 minutes.

[0139] In embodiments (e.g., where the binder of the functionalized fabric is applied to the fibrous fabric in the form of a dispersion comprising the binder or a solution comprising the binder), applying and / or adhering the binder to the fibrous fabric may include evaporating a liquid component of the binder or a solution comprising the binder.

[0140] Formed parts

[0141] The shaped component comprises a fabric laminate (eg, a consolidated fabric laminate) as described herein.

[0142] Formed parts can be produced by the following steps:

[0143] a) providing a fabric laminate as described herein;

[0144] b) shaping the fabric laminate; and

[0145] c) heating the formed laminate at a temperature of up to about 150°C.

[0146] In an embodiment, heating the fabric laminate comprises heating the fabric laminate at a temperature of at least about 50° C., such as at least about 60° C., at least about 70° C., at least about 80° C., at least about 90° C., or at least about 100° C. In an embodiment, heating the fabric laminate comprises heating the fabric laminate at a temperature of up to about 150° C., such as up to about 130° C., or up to about 120° C. In an embodiment, heating the fabric laminate comprises heating the fabric laminate at a temperature in the range of about 50° C. to about 150° C., such as about 70° C. to about 130° C., or about 80° C. to about 120° C.

[0147] In an embodiment, producing the formed part may include heating the fabric laminate at a temperature of up to about 150° C. and a pressure below atmospheric pressure, for example a pressure in the range of about 500 mbar to about 1000 mbar, or about 600 mbar to about 1000 mbar, about 700 mbar to about 1000 mbar, about 750 mbar to about 1000 mbar, about 800 mbar to about 1000 mbar, or about 900 mbar.

[0148] In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of up to about 5 hours, e.g., up to about 3 hours, up to about 2 hours, or up to about 1 hour, to form a shaped article. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of at least about 10 minutes, e.g., at least about 30 minutes, to form a shaped article. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of about 10 minutes to about 5 hours, e.g., about 30 minutes to about 2 hours or about 30 minutes to about 1 hour.

[0149] In an embodiment, shaping the fabric layup involves placing the fabric layup on or in a mold. In an embodiment, shaping the fabric layup involves placing the fabric layup on or in a mold and applying increased heat and / or reduced pressure to the fabric layup.

[0150] In embodiments, a shaped part described herein may be impregnated with a resin and the resin cured to form a composite article.

[0151] In an embodiment, the binder is selected to be compatible with the resin used to form the composite article. For example, where the functionalized fabric is to be incorporated into a composite article comprising an epoxy resin, an epoxy-compatible (e.g., epoxy-based) binder may be selected. For example, where the functionalized fabric is to be incorporated into a composite article comprising a polyester resin, a polyester-compatible (e.g., polyester-based) binder may be selected. The binder may be selected so that the binder is soluble in the resin used to form the composite article.

[0152] Consistency and quality control

[0153] The use of fluorescent binders according to the present disclosure provides one or more methods for evaluating the distribution of binders on fabrics, for example to evaluate and characterize the amount of binder dispersion and presence at the fabric surface. This may include evaluating whether the binder (e.g., binder particles) is evenly distributed, monitoring for defects, counting the particles of binder present (e.g., using image analysis), or incorporating a unique identifier. The inventors have found that fluorescent binders provide better contrast during production than when non-fluorescent binders are employed.

[0154] According to an eighth aspect of the present invention, there is provided a method for evaluating or detecting the presence or distribution of a binder (e.g., binder particles) on a functionalized fabric described herein by exposing the binder to light (e.g., UV light, e.g., light having a wavelength in the range of about 10 nm to about 400 nm, e.g., about 100 nm to about 400 nm, or about 200 nm to about 400 nm, or about 300 nm to about 400 nm, or about 250 nm to about 380 nm) to cause it to fluoresce. The fluorescent binder can be viewed, detected, or analyzed. For example, the fluorescent binder can be viewed, detected, or analyzed by eye with or without assistance. The fluorescent binder can be viewed by the human eye or by other devices (such as a fluorescence detector).

[0155] This method can be used as part of a manual or automated method, for example as part of a production line and for the purpose of quality control. Examples of quality control include online and offline quality control. Online quality control methods include checkpoints throughout the production line. These points can check the quality of the product according to various standards or specifications. Generally speaking, online quality control is faster than offline systems. This is mainly because the inspection is carried out as the method proceeds, without the need for additional disassembly or replacement time. The data obtained from these inspections can be used to modify and adjust the production method in real time, which can reduce waste and save time. The products and methods provided according to the present invention are particularly useful in online quality control.

[0156] The distribution of the adhesive can be verified without resorting to destructive testing but rather by exposure to UV light and without interrupting the production line, and thus increasing the efficiency of mass production.

[0157] Example

[0158] The following are examples of fabrics and related aspects described herein. Therefore, these examples should not be considered as limiting the present disclosure, but are only used to teach how to implement the methods of the present disclosure and obtain the products of the present disclosure.

[0159] Functionalized fabrics were produced by applying different amounts of binder to one surface of different fiber fabrics. The materials used are described below, and Table 1 summarizes each functionalized fabric of the Examples.

[0160] Fiber fabrics used in the examples

[0161] All fiber fabrics used in the examples are non-crimp fabrics and contain glass first fibers and glass second fibers, the first fibers and the second fibers being held in their respective orientations by stitching yarns. The glass fibers constituting the fiber fabrics contain an epoxy resin compatible sizing agent.

[0162] The unidirectional fiber fabrics used in these examples (indicated as "UD" in the table below) contain up to about 5% by weight of the second fibers (glass fibers) of the fiber fabric, and at least 95% by weight of the first fibers (glass fibers) of the fiber fabric, and the second direction is substantially perpendicular to the first direction. Unidirectional fabrics are referred to as "UD0", and UD0 fabrics contain first fibers oriented in the 0 direction (i.e., aligned with the length of the fabric). Functionalized fabrics including UD90 fabrics (fabrics containing first fibers oriented in the 90 direction (i.e., perpendicular to the length of the fabric)) can also be prepared.

[0163] Biaxial fiber fabrics can also be used to prepare functionalized fabrics as described herein. For example, functionalized fabrics comprising biaxial fiber fabrics can be prepared as described in the following examples. Examples of suitable biaxial fabrics include fabrics containing at least about 15% by weight of the second fiber (glass fiber) of the fiber fabric, with the second direction being substantially perpendicular to the first direction (these fabrics may be referred to as "BX90" fabrics) or at about 45 degrees to the first direction (these fabrics may be referred to as "BX45" fabrics).

[0164] The inventors contemplate that other fiber fabrics described herein for use in providing functionalized fabrics provide similar advantages as the fiber fabrics used in these examples.

[0165] Measurement method

[0166] The glass transition temperature of the binder was determined using differential scanning calorimetry (DSC) according to EN ISO 11357-2 (determination of the glass transition temperature) by heating the binder at a heating rate of 10 K / min from -60°C to 120°C at an air flow rate of 80 mL / min, then holding at 120°C for 5 minutes, then cooling from 120°C to -60°C at a cooling rate of 10 K / min, then holding at -60°C for 5 minutes, then heating again from -60°C to 120°C at a heating rate of 10 K / min. The glass transition temperature was determined as the value provided by the second heating cycle.

[0167] The volume average particle size of the binder particles applied to the fiber fabrics described in the following examples to provide functionalized fabrics was determined as follows: using a particle size analyzer (obtained from Beckman TM The dispersion of binder particles was subjected to dynamic light scattering using a LS13320 particle size analyzer from Sigma-Aldrich (Shanghai) and the dispersion of binder particles was subjected to dynamic light scattering using a LS13320 particle size analyzer from Sigma-Aldrich (Shanghai) according to the ISO 13320 2009 standard.

[0168] The shear modulus G of the adhesive used in the following examples at 30°C was determined using an oscillatory rheometer at 0.1% deformation and a frequency of 1 Hz in a plane-to-plane geometry using an adhesive sample having a thickness of 400 μm and a diameter of 25 mm, using a heating-cooling-heating cycle of heating from 30°C to 130°C at a heating rate of 3°C / min, cooling from 130°C to 30°C and heating from 30°C to 130°C at a heating rate of 3°C / min.

[0169] The dynamic viscosity η of the adhesive used in the following examples at 130°C was determined using an oscillatory rheometer at 0.1% deformation and a frequency of 1 Hz in a plane-plane geometry using an adhesive sample having a thickness of 400 μm and a diameter of 25 mm, using a heating-cooling-heating cycle, which is heated from 30°C to 130°C at a heating rate of 3°C / min, cooled from 130°C to 30°C and heated from 30°C to 130°C at a heating rate of 3°C / min.

[0170] Binder resin

[0171] Resin binder Polyester-based binder particles purchased from Coim TM , having a glass transition temperature of 46°C (determined using DSC as described above), a softening point of 57°C (determined using an oscillatory rheometer according to the method described above), and a volume average particle size of about 185 μm (determined by using a particle size analyzer (obtained from Beckman TM LS13320) determined using dynamic light scattering, see also Figure 1, line C), a shear modulus G at 30°C of 30.7 MPa (determined using an oscillatory rheometer as described above), a dynamic viscosity η at 130°C of 387 Pa.s (determined using an oscillatory rheometer as described above), a molecular weight Mw of 185710, and a polydispersity of 28.87 (determined as Mw / Mn). The polyester binder employed contains a fluorescent material that fluoresces in response to UV light.

[0172] Table 1

[0173]

[0174] The functionalized fabrics of Examples 1 to 4 were provided in the following manner: the resin binder in the amount shown in Table 1 was applied to the above fiber fabric, and after the resin binder was applied to the fiber fabric, it was heated to a temperature of 110° C. (a temperature higher than the melting temperature of each resin binder) for 1 minute, and then cooled to room temperature to adhere the binder particles to the surface of the fiber fabric. Figure 2 An example of an image (taken using a 3D microscope) of the surface of a functionalized fabric as described herein is shown, in which binder particles have been attached to the surface of the fiber fabric by melting and solidification (by cooling) of the binder particles. Figure 2 As can be seen in FIG. 1 , the functionalized fabric comprises binder particles (discrete binder particles) adhered to the surface of the fiber fabric, and the binder particles are spaced apart from each other, i.e., there is a fiber fabric surface area without binder particles around each binder particle.

[0175] Figure 3a and Figure 3b An example of an image of fluorescent binder particles on a fiber fabric surface taken under UV light having a wavelength of 365 nm in relation to Examples 1 and 2 is shown. The image shows that a uniform distribution of binder particles has been provided. The sample was also viewed under UV light having a wavelength of 254 nm to provide a uniform distribution of the binder particles. Figure 3a and Figure 3b Images similar to those shown were found to be brighter when viewed under UV light having a wavelength of 365 nm than when viewed under UV light having a wavelength of 254 nm, the brighter images providing improvements in image analysis.

[0176] Figure 4a An example of an image of the surface of a functionalized fabric produced according to Example 2 (taken using a 3D microscope) is shown. Figure 4b It is shown Figure 4a The particle size distribution of the binder on the surface of the functionalized fabric is shown in the figure. TM Optical microscope) and related image analysis software (ImageJ software) to calculate the 10 mm2 The binder particle size distribution over the area is determined to thereby determine the binder particle size distribution showing the range of the longest axial length of each adhered binder particle.

[0177] Wear test

[0178] The adhesion strength between the fiber fabric and the adhered binder particles of the functionalized fabric of Example 3 was determined using a scrub test (Elcometer 1720 Abrasion Tester) according to ISO 11998-2006. The test was carried out without liquid using three abrasives: microfiber fabric, Scotch-Brite TM Type 7446 pad and sandpaper grade 100. Weight of the abrasive pad with stand is 455 g. Scrubbing surface is 300 mm. 200 runs (back and forth) are performed. For each functionalized fabric tested, the following results are obtained:

[0179] Scrub Test Using Microfiber Fabric - No effect on adhesive adhesion and no weight loss. Slight visual changes were noted where the fabric was abraded.

[0180] Using Scotch-Brite TM Scrub Test with Type 7446 Pad - No effect on adhesive adhesion and no weight loss. Slight visual changes were noted where the fabric was worn.

[0181] Scrub test with sandpaper P100 - the fabric was destroyed. After only 5 to 10 runs, fuzz began to appear. It was found that the binder remained within the fuzz glass. This indicates that the adhesion between the adhered binder particles and the fiber fabric is greater than the abrasion resistance of the fiber fabric.

[0182] The inventors contemplate that other functionalized fabrics described herein will exhibit similar abrasion resistance.

[0183] The functionalized fabric of each example was found to handle very well with no detached adhesive.

[0184] The functionalized fabrics were then formed into a fabric laminate by stacking 5 to 20 layers, and each of the functionalized fabrics of Examples 1 to 4 formed a different fabric laminate.

[0185] Each type of fabric layup was then shaped using a mould and heated under reduced pressure of about 900 mbar for a period of about 30 minutes to 1 hour. It was found that at temperatures in the range of 50°C to 100°C, each fabric layup was successfully consolidated to form a shaped part (i.e., a part that remained in the form of the mould even after being removed from the mould) within this relatively short period of time, with a temperature of about 100°C providing the most sharply defined shaped part.

[0186] Each shaped part formed from the different functionalized fabrics was then infused with polyester resin. A sample of each fiber fabric used in Examples 1 to 4 to which a binder had not been applied was also infused with polyester resin for comparison. The resin-infused shaped parts were cured to form composite articles.

[0187] It was found that shaped parts formed from the functionalized fabrics of Examples 1 to 4 exhibited excellent infusion rates, and in fact exhibited faster infusion rates than corresponding fiber fabrics without a binder.

[0188] The mechanical properties (e.g., shear and strength properties in the 0° (first direction), 45°, and 90° directions) of composite articles comprising the functionalized fabrics of Examples 1 to 4 were found to be comparable to those of composite articles comprising corresponding fiber fabrics without a binder.

[0189] The inventors also prepared and tested functionalized fabrics similar to those described above, but without using a series of other fiber fabrics described herein to provide the functionalized fabrics. These additional functionalized fabrics were found to provide similar advantages to the fiber fabrics employed in these examples.

[0190] In addition, the inventors have discovered that the fabric layups or formed parts described herein can be used to significantly improve the layup speed of a composite article comprising the formed parts described herein. For example, formed parts comprising the functionalized fabrics described herein can be employed during the manufacture of wind turbine blades by incorporating the formed parts directly into the wind turbine blades during the layup process.

[0191] The features disclosed in the foregoing description or in the following claims or in the accompanying drawings, expressed in their specific form or in terms of means for performing the disclosed functions or methods or processes for obtaining the disclosed results, may, where appropriate, be used alone or in any combination of these features to realize the invention in its various different forms.

[0192] Although the present invention has been described in conjunction with the above exemplary embodiments, many equivalent modifications and variations will be apparent to those skilled in the art when this disclosure is given. Therefore, the exemplary embodiments of the present invention set forth above are considered to be illustrative rather than restrictive. Various changes may be made to the described embodiments without departing from the spirit and scope of the present invention.

[0193] For the avoidance of any doubt, any theoretical explanations provided herein are intended to enhance the reader's understanding. The inventors do not wish to be bound by any of these theoretical explanations.

[0194] Any section headings used herein are for organizational purposes only and are not to be construed as limiting the subject matter described.

[0195] Throughout this specification, including the claims that follow, unless the context requires otherwise, the words "comprise" and "comprising" and variations such as "have" and "containing", will be understood to imply the inclusion of stated integers or steps or groups of integers or steps but not the exclusion of any other integers or steps or groups of integers or steps.

[0196] It must be noted that, as used in the specification and the appended claims, the singular forms "a", "an", and "the" include plural referents unless the context clearly indicates otherwise. Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about", it should be understood that the particular value forms another embodiment. The term "about" in relation to a numerical value is optional and means, for example, + / - 10%.

Claims

1. A functionalized fabric comprising: Fabrics; and a binder, the binder containing a fluorescent material, The fiber fabric comprises: first fibers oriented along a first direction; and second fibers oriented along a second direction, wherein the first fibers include glass fibers and / or carbon fibers, the second fibers include glass fibers and / or carbon fibers, and the second direction is within 0 to 90 degrees of the first direction.

2. The functionalized textile of claim 1, wherein the fluorescent material fluoresces in response to UV light.

3. The functionalized fabric according to any one of claims 1 or 2, wherein the fluorescent material is present in an amount of up to about 5 wt % based on the total weight of the functionalized fabric.

4. The functionalized fabric according to any one of claims 1 to 3, wherein the binder has a glass transition temperature of at most about 75°C.

5. The functionalized fabric of any one of claims 1 to 4, wherein the binder comprises from about 0.1 wt% to about 3.5 wt% of the functionalized fabric.

6. The functionalized fabric according to any one of claims 1 to 5, comprising about 2 g / m 2 About 30g / m 2 of the binder.

7. The functionalized fabric according to any one of claims 1 to 6, wherein the binder comprises a polymer resin containing epoxy, acrylate or ester functional groups.

8. The functionalized textile according to any one of claims 1 to 7, wherein the binder consists of or consists essentially of a fluorescent material.

9. The functionalized textile according to any one of claims 1 to 8, wherein at least the first fiber or the second fiber is glass fiber, or wherein both the first fiber and the second fiber are glass fiber.

10. The functionalized fabric according to any one of claims 1 to 9, wherein the fiber fabric is a non-crimp fabric and the functionalized fabric comprises stitching yarns, wherein the stitching yarns hold the first fibers and the second fibers in their respective orientations.

11. The functionalized textile according to any one of claims 1 to 10, wherein the binder comprising fluorescent material is in the form of binder particles.

12. A fabric laminate comprising at least two layers of the functionalized fabric according to any one of claims 1 to 11, wherein one layer of the functionalized fabric according to any one of claims 1 to 11 is directly disposed on another layer of the functionalized fabric according to any one of claims 1 to 11.

13. A shaped part comprising a fabric laminate according to claim 12.

14. A method for producing a functionalized fabric, the method comprising: Providing a fiber fabric, the fiber fabric comprising first fibers oriented in a first direction and second fibers oriented in a second direction, the second direction being within 0 to 90 degrees of the first direction, the first fibers comprising glass fibers and / or carbon fibers, and the second fibers comprising glass fibers and / or carbon fibers; and A binder including a fluorescent material is applied to the fiber fabric to provide the functionalized fabric.

15. The method of claim 14, further comprising exposing the adhesive to UV light.

16. The method according to claim 15, wherein the method is part of an online quality control method.

17. A method for producing a shaped part, the method comprising: stacking multiple layers of the functionalized fabric according to any one of claims 1 to 11 to provide a fabric laminate; shaping the fabric laminate; as well as The fabric laminate is heated at a temperature of up to about 150°C.

18. A method of evaluating the distribution of a fluorescent binder on a functionalized fabric according to any one of claims 1 to 11, wherein the binder is exposed to UV light to cause the binder to fluoresce.

Citation Information

Patent Citations

  • Improvements in or relating to fibre reinforced composites

    CN104812567A

  • Infusible unidirectional fabric

    CN104955996A

  • Hybrid reinforcement fabric

    CN112585309A

  • Methods and apparatus for reducing load in a rotor blade

    CN1904353A

  • Method for identifying origin of and detecting defects in glass and quartz fiber products

    US20040009724A1